Clival Osteomyelitis Presenting as a Skull Base Mass - Michalowicz, Matthew; Ramanathan, Murugappan, Jr (Journal of Neurological Surgery Reports, 2017)
Central skull base osteomyelitis is a rare, but potentially life-threatening disease entity often lacking otologic symptoms or external auditory canal pathology. We present a case of a man in his 70s who had developed cranial nerve deficits with radiographic evidence that was consistent with a tumor due to this uncommon entity. The radiologic findings and our experience are discussed to increase awareness in the otolaryngology community.
Keywords: clival osteomyelitis; skull base mass; skull base osteomyelitis; central skull base osteomyelitis